THE ROLE OF ENVIRONMENT DEVELOPMENT ON INSTITUTIONAL ACCOUNTING IN INDONESIA - Hadori Yunus (Journal of Indonesian Economy and Business (JIEB), 2000)
Some accounting rules and conventions sometimes are inappropriate, and misleading in the sense that they are unsuited to the needs of the accounting profession. Related to that experience, Indonesia should learn from its own experiences, which were originally influenced by the Dutch and have since become strongly influenced by the United States of America (USA). This paper elaborated the Indonesian accountancy system on aspects of the environment, accounting principles and EFR practices. The environment factors are included such as economic, legal, social, political, and cultural aspects. Those aspects and intersection among them will be critically analyzed. The focus of interpretation and critical thinking will be in formulating accounting development strategy, as well as strategizing a relationship between accounting education and accounting profession. The influence of political, legal and economic has a significant share on policies’ setting in accounting theories and practices. For example, capital market institutions and practices promoted some accounting requirements to impose a quality standard in market accountability. This means there are a political, legal and economical support for implementing External Financial Reporting (EFR)’s approach, especially on greater disclosure and toward globalization incentives.